Atmospheric deposition of lead in remote high mountain of eastern Tibetan Plateau, China - Bing, Haijian; Wu, Yanhong; Zhou, Jun; Ming, Lili; Sun, Shouqin; Li, Xiangdong (Atmospheric environment (1994), 2014)
Global warming has induced visible glacier retreat on many high mountains. The glacier forelands with the chronosequence and vegetation succession offer a good opportunity to assess natural (e.g., mineral weathering) and anthropogenic influence on trace element geochemical cycling in high mountain ecosystems. In the present study, the concentrations and isotope composition of lead (Pb) in soil profiles and mosses from the Hailuogou Glacier foreland in eastern Tibetan Plateau were investigated. The enrichment of Pb in the O and A horizons of soil layers and mosses indicated the influence from recently atmospheric deposition, while the local soil parent materials mainly affected the C horizon of soils. The lower 206Pb/207Pb (1.160–1.180) and higher 208Pb/206Pb (2.092–2.120) ratios were observed in the O horizon in comparison with the A (1.171–1.209 and 2.042–2.108, respectively) and C (1.183–1.206 and 2.070–2.130, respectively) horizons. The Pb isotope composition in the mosses was similar to those of the O horizon. The Pb-ore-involved industries and coal combustion in southwest China and South Asia were identified as the major sources of anthropogenic Pb at the glacier foreland. The estimations using binary mixing model indicated that the anthropogenic Pb contribution was about 45.2–61.3% for the O horizon, 8.6–34.8% for the A horizon, and 41.6–65.9% for the mosses. The results indicated that the anthropogenic Pb could reach the remote high mountains of eastern Tibetan Plateau through long distance atmospheric transport. •Lead concentrations in soil profiles and mosses were investigated in the remote high mountain of eastern Tibetan Plateau.•Lead sources were quantitatively identified by Pb isotope composition and air mass trajectory.•Lead-ore-involved industries and coal combustion in southwest China and South Asia were the major sources of anthropogenic Pb.•Anthropogenic Pb was 45.2–61.3% in surface soils and 41.6–65.9% in mosses.